Identifikasi Hama Pada Kayu Cendana (Santalum album Linn) di Hutan Pendidikan dan Pelatihan Sisimeni Sanam Kabupaten Kupang - Sakan, Ritwan; Seran, Wilhelmina; Mau, Astin Elise (Wana Lestari, 2022)
Sandalwood (Santalum album Linn) is an important tipes of forest plant in East Nusa Tenggara because it has high economic value and the best endemic species in the world. Sandalwood produces essential oils with a widely and popular fragrant aroma, so it has a fairly good market value. The sandalwood population is decreasing day by day and becomes a rare plant, caused by the setting of high annual logging targets, high theft and lack of balance with the success of good regeneration through plantation forests and natural forests. Pests are also an inhibiting factor in sandalwood cultivation. This study aims to determine the types of pests, the frequency of attacks and the intensity of damage in Sisimeni Sanam Education and Training Forest. This research was carried out from December 2019 until January 2020 in Sisimeni Sanam Education and Training Forest, and Pest Laboratory, Faculty of Agriculture, Nusa Cendana University. Pests that damage Sandalwood (Santalum album Linn) crops in Sisimeni Sanam Education and Training Forest are: Yellow Beetle (Hypomeces Squamosus), White Flea (Ferrisia virgata), Caterpillar (Artocornis Submarginata). Pests that have the potential to damage Sandalwood (Santalum album Linn) plants in the long time are Walang Sangit (Leptocorisa spp). There were 133 plants attacked from 185 plants observed. The results shows the attack frequency are 72 % which is categorized as severe attack. Damage intensity is known that 41,5 % which is categorized as Moderate Damage.